PENGARUH PERPUTARAN KAS, PIUTANG USAHA DAN PERSEDIAAN TERHADAP TINGKAT PROFITABILITAS PERUSAHAAN OTOMOTIF DAN KOMPONENNYA YANG TERDAFTAR DI BURSA EFEK INDONESIA - B11108074, Arpensius (Jurnal Manajemen Update, 2015)
The objective of the research is finding out whether the asset turnover, Account Receivable Turnover and Inventory Turnover influence the profitability both partially and stimulatingly. The object chosen by the researcher is automotive industry companies which components are registered on Indonesian Stock Exchange. Research method on this thesis is Causal Research; with the number of samples is 10 companies from 17 automotive industry companies registered on Indonesian Stock Exchange. The research is conducted for the observation in 2006-2013. The type of data is seconder data. The data is gathered from Indonesian Stock Exchange’s official site and ICMD. Then collected data is analyzed by using data analysis method, which has been tested with classical assumption before the hypothesis testing. Hypothesis testing in this research uses double linear regression analysis with t testing and f testing on the significant level of 5% (α = 0,05). The result of Hypothesis testing shows that Partial Variable of Asset turnover and Account Receivable Turnover is influential against Profitability and Inventory Turnover has positive influence, but not significant, against Profitability. Stimulatingly, Asset turnover, Account Receivable Turnover and Inventory Turnover is influential against profitability. Where 18,8% of variation from profitability changes can be explained by the variation of both of independent variable, whereas the rest, on the number of 81,2% is explained by the variation and other factors which are not including on the regression model. Keywords : Asset turnover, Account Receivable turnover, Inventory turnover and profitability